Seasonal variation of ewe body condition in extensive production systems of northeastern Portugal - Azevedo, Jorge Manuel Teixeira de (2009)
During four years, 2 flocks of autochthonous Churra Galega Bragançana (CB) and Churra da Terra Quente (CTQ) breeds with 87 ± 29 and 93 ± 13 ewes were studied. These flocks are managed in the traditional extensive systems followed in the Northeast of Portugal. The body condition score (BCS) was recorded monthly using the method proposed by Russel et al. (1969). The results for both flocks show that BCS in 9 to 12 months are below note 3 in more than 73% of the ewes. The better BCS was observed at the spring (55 and 43% of ewes with BCS of 3 or 4 for CB and CTQ, respectively). The results show that the traditional production system allows significant seasonal body condition variation and low body condition of ewes during a great part of the year.